1978
DOI: 10.1007/bf01939677
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the mouse from genetic radiation damage by an optimal-dose-ratio combination of ATP, AET, and serotonin

Abstract: The study concerned antiradiation effects in germ-cell genetic structures produced by a combination of ATP, AET, and serotonin at dose ratio optimal for lethality namely, 45:3:1, as arrived at in our previous work. Such a combination was found to reduce by a factor of 2 the translocation yields observed after 400 R X-rays to mouse spermatogonia. In terms of animal survival, ATP has been shown to contribute little to total protection achieved by the same combination; in terms of genetic damage; however, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Less than 1 % of the activity was measured in 7 of the 10 clamped tumours tested, which was interpreted as evidence that the occlusion of the blood vessels was effective. ATP has been shown to modify the response to radiation in several situations [12][13][14], But this response following ionising radiation is dependent upon adequate cellular supply, availability and utilisation of energy. Nagle et al [5] demonstrated that V79 Chinese hamster cells depleted in ATP were unable to rejoin X-ray-induced DNA strand breaks.…”
Section: Resultsmentioning
confidence: 99%
“…Less than 1 % of the activity was measured in 7 of the 10 clamped tumours tested, which was interpreted as evidence that the occlusion of the blood vessels was effective. ATP has been shown to modify the response to radiation in several situations [12][13][14], But this response following ionising radiation is dependent upon adequate cellular supply, availability and utilisation of energy. Nagle et al [5] demonstrated that V79 Chinese hamster cells depleted in ATP were unable to rejoin X-ray-induced DNA strand breaks.…”
Section: Resultsmentioning
confidence: 99%